2020
DOI: 10.1021/acsomega.0c03845
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Antioxidant Compounds in Riboflavin-Mediated Photo-Oxidation of Methionine: A 1H-NMR Approach

Abstract: Riboflavin (RF) is a well-known photosensitizer, responsible for the light-induced oxidation of methionine (Met) leading to the spoilage of wine. An NMR approach was used to investigate the role of gallic acid (GA) and sulfur dioxide (SO 2 ) in the RF-mediated photo-oxidation of Met. Water solutions of RF and Met, with and without GA or SO 2 , were exposed to visible light for increasing time in both air and nitrogen atmospheres. Upon light exposure, a new signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 39 publications
(90 reference statements)
3
25
0
Order By: Relevance
“…Differently, the decrease of Met was dependent on the additives added and ranged from −24% in MW+SO 2 and MW+SO 2 +GSH samples up to −100% in MW+GSH and MW+CT+GSH samples (Table 1). Among compounds expected to arise from the oxidation of Met [36], only Met sulfoxide was found, in accordance with the previous study carried out by NMR [21]. The absence of this compound in MW samples without additives allowed to exclude the possible oxidation of Met by the acidic environment or matrix components.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Differently, the decrease of Met was dependent on the additives added and ranged from −24% in MW+SO 2 and MW+SO 2 +GSH samples up to −100% in MW+GSH and MW+CT+GSH samples (Table 1). Among compounds expected to arise from the oxidation of Met [36], only Met sulfoxide was found, in accordance with the previous study carried out by NMR [21]. The absence of this compound in MW samples without additives allowed to exclude the possible oxidation of Met by the acidic environment or matrix components.…”
Section: Resultssupporting
confidence: 90%
“…Met content decreased in WW samples containing both GSH and SO 2 (−21%) or SO 2 only (−38%) (Table 3), suggesting the influence of the antioxidants on photo-degradative mechanisms and their competition with Met in both Type I and Type II pathways [13,17,21].…”
Section: Storage In the Dark After Light Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the dark interaction Rf-FUR, steady-state fluorescence studies confirm that FUR is associated with Rf in the ground state. This dark complex possesses an association constant (Kas =1.8 ± 0.2 M -1 , process (19)). In addition to this, a 1 k q = 2.7 10 9 M -1 s -1 value for the dynamic component of 1 Rf* quenching by FUR was obtained by fluorescence lifetime experiments.…”
Section: Homogeneous Mediummentioning
confidence: 99%
“…[16][17][18] For example, different studies have reported the Rf-photosensitization of antioxidants, flavorings, or J o u r n a l P r e -p r o o f 5 food-related substances. [19][20][21][22] Nevertheless, no previous study has reported the Rf-photosensitization of FUR in homogeneous media or CDs solutions. FUR, Rf, and -cyclodextrin (βCD) coexist in a wide variety of formulations.…”
Section: Introductionmentioning
confidence: 99%